TAREKAT SUFIYAH ISLAM DALAM PEMIKIRAN TASAWUF H. ABDUL MUIN HIDAYATULLAH - Murjani Sani (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
This paper describes only the existence of Islamic Sufiyah tarekat (TSI) in the thought of H. Abdul Muin Hidayatullah. The results show that the TSI was built by H. Abdul Muin since 1955 after he was brought into a spiritual meeting with Rasulullah, Prophet Adam and Moses as well as 40 leaders of an Islamic state. At that time, he had been inducted as a murshid Zabir tarekat, while Murshid is the Messenger of Allah. That's when it started developing tarekat until he passed away, 1995 at the age of 87 years. Murshid was replaced by his own son, K.H. Abdullah al-Mahdi and develop it until now. The Islamic Sufiyah Tarekat is growing quite rapidly; reaching 7,000 people are now members, consisting of listeners, students, followers and supporters. They spread in South Kalimantan, especially in Banjarmasin, and in the District Tabunganen Tabalong, and actively carry out the teaching daily deed specified. It is in meaningful, positive impact on the development of faith and piety of its members.